Direct heating containment vessel interactions code (DHCVIC) and prediction of SNL ''SURTSEY'' test DCH-1 - Ginsberg, T.; Tutu, N. (Brookhaven National Lab., Upton, NY (USA). Nuclear Energy Dept., 1986)
High-pressure melt ejection from PWR vessels has been identified as a severe core accident scenario which could potentially lead to ''early'' containment failure. Melt ejection, followed by dispersal of the melt by high velocity steam in the cavity beneath the PWR vessel could, according to this scenario, lead to rapid transfer of energy from the melt droplets to the containment atmosphere. This paper describes DHCVIC, an integrated model of the thermal, chemical and hydrodynamic interactions which are postulated to take place during high-pressure melt ejection sequences. The model, which characterizes vessel (or building), is applied to prediction of the Sandia National Laboratory ''SURTSEY'' Test DCH-1 and a (post-test) prediction of that test is made.